Nonlinear statistical modeling proceedings of the thirteenth International Symposium in Economic Theory and Econometrics : essays in honor of Takeshi Amemiya - Amemiya, Takeshi; Hsiao, Cheng 1943-; Morimune, Kimio; Powell, James 1955- (International symposia in economic theory and econometrics, 2000)
This collection brings together important contributions by leading econometricians on (i) parametric approaches to qualitative and sample selection models, (ii) nonparametric and semiparametric approaches to qualitative and sample selection models, and (iii) nonlinear estimation of cross-sectional and time series models. The advances achieved here can have important bearing on the choice of methods and analytical techniques in applied research. The collection is dedicated to Professor Takeshi Amemiya in honor of his path-breaking contributions to econometrics and statistics.